2014
DOI: 10.1038/ncomms5221
|View full text |Cite
|
Sign up to set email alerts
|

Development of oculomotor circuitry independent of hox3 genes

Abstract: Hox genes have been shown to be essential in vertebrate neural circuit formation and their depletion has resulted in homeotic transformations with neuron loss and miswiring. Here we quantifiy four eye movements in the zebrafish mutant valentino and hox3 knockdowns and find that contrary to the classical model, oculomotor circuits in hindbrain rhombomeres 5-6 develop and function independently from hox3 genes. All subgroups of oculomotor neurons are present as well as their input and output connections. Ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 65 publications
5
17
0
Order By: Relevance
“…Others have used genetic manipulation of hindbrain patterning genes to provide some evidence of flexibility and robustness in the developmental program, by studying the functional properties of ectopically induced neurons [32,33] and populations developing in the absence of normal segmental gene expression [34]. Indeed, a previous study in mice [35] provided indirect evidence that a mutation blocking FBMN caudal migration also extended the rostrocaudal range of the embryonic parafacial oscillator (e-pF) and spared specific features of respiratory connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used genetic manipulation of hindbrain patterning genes to provide some evidence of flexibility and robustness in the developmental program, by studying the functional properties of ectopically induced neurons [32,33] and populations developing in the absence of normal segmental gene expression [34]. Indeed, a previous study in mice [35] provided indirect evidence that a mutation blocking FBMN caudal migration also extended the rostrocaudal range of the embryonic parafacial oscillator (e-pF) and spared specific features of respiratory connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, even when circuits achieve their normal function despite some developmental perturbation, they may be vulnerable to dysfunction in specific contexts. For example, Ma et al [34] found that disruption of normal segmental gene expression in valentino zebrafish mutants resulted in sporadic, aberrant oculomotor behaviors (correlated with jaw and fin movements) layered on top of normal horizontal eye movements. The authors concluded that normal segmental signaling may protect developing circuits from aberrant connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To locate the border between r6 and r7 we followed a similar approach that was performed previous using light microscopic imaging and the expression of the hox genes [55, 49, 29]. Briefly reticulospinal cells were identified based on the ultrastructure, that was very different form the remaining cells in the area.…”
Section: Star Methods Textmentioning
confidence: 99%
“…Halorhodopsin was locally activated via a 565 nm light-emitting diode (LED) coupled to a 100 μm optic fiber (Figure 2A; Supplemental Experimental Procedures) that was positioned unilaterally roughly above rhombomere 5, which was previously found to affect directional saccade generation in zebrafish when optogenetically inhibited (Schoonheim et al., 2010). This location likely corresponds to the nucleus abducens (Ma et al., 2014). …”
Section: Resultsmentioning
confidence: 94%